Mathematics
Pana235
2016-04-13 12:05:36
Given: F = {(0, 1), (2, 4), (4, 6), (6, 8)} and G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)} (F + G) (2) = Given: F = {(0, 1), (2, 4), (4, 6), (6, 8)} and G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}(F - G) (6) = Given: F = {(0, 1), (2, 4), (4, 6), (6, 8)} and G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}(F  G) (2) =
ANSWERS
nancy18andrade
2016-04-13 15:10:36

(f + g) (2) = f (2) + g (2) = 4 + 5 = 9(f - g) (6) = f (6) - g (6) = (input the chosen values)(fg) = f*g = (input the chosen values)If this helps give a brainliest ;)

ADD ANSWER